Thirty‐Five‐Year Presence of African Swine Fever in Sardinia: History, Evolution and Risk Factors for Disease Maintenance. Issue 2 (12th September 2014) - Mur, L.; Atzeni, M.; Martínez‐López, B.; Feliziani, F.; Rolesu, S.; Sanchez‐Vizcaino, J. M.
Summary: Despite the implementation of control efforts and funds to fight against the disease, African swine fever (ASF) has been present in Sardinia since 1978. It has caused serious problems for both the industrial pig sector and the regional authorities in Sardinia, as well as the economy of Italy and the European Union, which annually supports the costly eradication programme. During this time, ASF has persisted, especially in the central‐east part of Sardinia where almost 75% of the total outbreaks are concentrated. The Sardinian pig sector is clearly divided into two categories based on the specialization and industrialization of production: industrial farms, which represents only 1.8% of the farms in the island and non‐professional holdings, which are comprised of small producers (90% of pig holdings have <15 pigs) and apply little to no biosecurity measures. Additionally, illegally raised pigs are still bred in free‐ranging systems in certain isolated parts of the island, despite strict regulations. The illegal raising of pigs, along with other high‐risk management practices (e.g. use of communal areas) are likely the primary reasons for endemic persistence of the virus in this area. The compensation provided to the farmers, and other aspects of the eradication programme have also negatively influenced eradication efforts, indicating that socio‐cultural and economic factors play an important role in the epidemiology of ASF on the island. The aim of this study was to comprehensively review the evolution of the 35‐year presence of ASF in Sardinia, including control measures, and the environmental and socio‐economic factors that may have contributed to disease endemicity on the island. The present review highlights the need for a coordinated programme that considers these socio‐economic and environmental factors and includes an assessment of new cost‐effective control strategies and diagnostic tools for effectively controlling ASF in Sardinia.